Utility of esophageal manometry and pH-metry in gastroesophageal reflux disease before surgery - Filiz AKYÜZ,; Serpil ARICI,; Fatih ERMİŞ,; Zeynel MUNGAN, (Turkish Journal of Gastroenterology, 2019)
-